Researching and Teaching Asian and Hong Kong Private International Law - Lui, Wilson (Indonesian Journal of International Law, 2023)
This article considers how private international law in Asia and Hong Kong is developing and should be developed, through both theoretical and practical aspects as evidenced in both research and teaching. It considers what is entailed when speaking of the concept of an “Asian private international law”, looking at it from the lens of researching and teaching Asian law with Asia “as a method” – calling for Asian law to be recognised as an equal to its Western counterpart and to be developed through a comparative analysis among Asian jurisdictions themselves and the pluralistic traditions they employ. It also discusses the development of “Asian private international law” through the current academic literature and the work of various international and regional organisations to date. The article then examines what is required to equip students in the classroom with the ability to truly appreciate the nature of “Asian private international law” by looking at the situation in Hong Kong, where the author designs and delivers a course on private international law at the University of Hong Kong. It reflects on three key improvements that can be made to courses in order to achieve that goal and considers the potential implications this experience of teaching in Hong Kong might have for other Asian universities. This article concludes with future directions and outlooks for Asian and Hong Kong private international law.